2016
DOI: 10.2298/stnv160912005b
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of early motherhood: Breastfeeding difficulties and life satisfaction

Abstract: Many studies have looked at benefits of breastfeeding for the baby and, less frequently, the mother. Though many women find breastfeeding difficult, few studies have looked at the potential costs of breastfeeding for this group. From January 19th 2015 through April 18th 2015, the total of 1,980 Serbian mothers completed an on-line survey consisting of 74 questions which addressed their satisfaction with various areas of life. Mothers were divided into four groups depending on their breastfeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4,5 The most recent WHO position paper stating that promotion of breastmilk substitutes and complementary foods undermines breastfeeding (including "growing-up milks" advertised for older children) is likewise consistent with the view that breastfeeding attitudes play a significant role in the decision to breastfeed and the duration of breastfeeding. 6 In line with this, attitudes toward breastfeeding in public have been given an increased importance as a research subject.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…4,5 The most recent WHO position paper stating that promotion of breastmilk substitutes and complementary foods undermines breastfeeding (including "growing-up milks" advertised for older children) is likewise consistent with the view that breastfeeding attitudes play a significant role in the decision to breastfeed and the duration of breastfeeding. 6 In line with this, attitudes toward breastfeeding in public have been given an increased importance as a research subject.…”
Section: Introductionmentioning
confidence: 74%
“…While welfare/family policies and public health initiatives remain an important consideration in breastfeeding success 1 , recent studies have also shown a link between breastfeeding attitudes and infant feeding choices 2 , perceived breastfeeding efficacy 3 and duration of breastfeeding 4 , thus shifting the focus from socio-demographic, institutional and biomedical factors to psychological and psychosocial factors and attitudes. 4,5 The most recent WHO position paper stating that promotion of breastmilk substitutes and complementary foods undermines breastfeeding (including "growing-up milks" advertised for older children) is likewise consistent with the view that breastfeeding attitudes play a significant role in the decision to breastfeed and the duration of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation